2022
DOI: 10.1038/s41420-022-01064-8
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Receptor-1 suppresses M2 macrophage polarization in colorectal cancer by downregulating EGFR

Abstract: Cannabinoid receptors, CB1 and CB2, have been implicated as emerging targets for cancer therapy. Herein, we investigated the potential regulation mechanism of CB1 and its implications in colorectal cancer. CB1 and EGFR expression were examined in colorectal cancer cell lines. The effects of CB1 agonist ACEA and its antagonist AM251 on the proliferation, migration and invasion of colorectal cancer cells and the expression of M1 and M2 macrophage markers were examined. EGFR overexpression was performed with plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Another study revealed that EGFR silencing inhibits TNBC cell proliferation and increase apoptosis through the suppression of STAT3 (Song et al, 2020b). Nude mouse tumor formation assays verified that EGFR silencing could suppress tumor cell growth (Song et al, 2020b;Deng et al, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…Another study revealed that EGFR silencing inhibits TNBC cell proliferation and increase apoptosis through the suppression of STAT3 (Song et al, 2020b). Nude mouse tumor formation assays verified that EGFR silencing could suppress tumor cell growth (Song et al, 2020b;Deng et al, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…CB1Rs are immunomodulators in macrophages [ 51 , 53 ], T cells [ 52 , 54 ], neutrophils [ 55 ], mast cells [ 56 ], and dendritic cells [ 57 ].…”
Section: Cannabinoid Receptors and Immunomodulationmentioning
confidence: 99%
“…CB2Rs regulate cytokines and ROS production, cell proliferation, apoptosis, and phagocytosis [ 17 , 53 , 54 , 90 , 92 , 93 , 94 ]. These effects occur via signal transduction pathways such as adenylyl cyclase inhibition, p38 and ERK1/2 activation, and nuclear factor kappa B (NF-κB) [ 17 , 70 , 94 ].…”
Section: Cannabinoid Receptors and Immunomodulationmentioning
confidence: 99%
“…IL-4, IL-13, CD206, Fizz1, and PPARγ protein levels are blocked by fenretinide, which finally inhibits M2 polarization without any effect on M1 polarization. Cannabinoids can modulate macrophage activity by reducing the expression of TNFα and IL-1β, suggesting its anticancer potential in xenograft tumors for colorectal cancer cells (HTC116, SW480, SW620, and HT29) [162,180]. Echinacea, on the other hand, enhances cytokine production (TNF-α, IL-1, IFN-β), activates macrophages by increasing the expression of CD80, CD86, MHCII molecules, and phagocytosis in murine bone marrow-derived macrophages [165,181].…”
Section: Regulation Of the Innate Immune Response In Cancer By Phytoc...mentioning
confidence: 99%